1994
DOI: 10.1111/j.1365-2141.1994.tb04829.x
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 8q due to i(8q) or der(8) t(8;8) is a frequent lesion in T‐prolymphocytic leukaemia: four new cases and a review of the literature

Abstract: Cytogenetic abnormalities found in four cases of T-cell prolymphocytic leukaemia (T-PLL) are described. An isochromosome 8q was found in three patients and a t(8;8) in one. In the four cases, karyotypes were complex and showed a high degree of instability. In addition, we reviewed 27 published cases of cytogenetically studied T-PLL. On the whole, the most frequently recurring anomalies in T-PLL are 14q lesions with nonrandom breakpoints, inversion (14)(q11q32) or tandem translocations (14;14) (not seen in any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 34 publications
2
22
1
Order By: Relevance
“…Deletions of 12p have also been found in T-PLL, using FISH and LOH methods, with a frequency of 43% (Salomon-Nguyen et al, 1998;Hetet et al, 2000). Finally, recurrent deletions or translocations of chromosome arms 6q, 13q, 17p, and monosomy 22 have occasionally been reported by standard cytogenetics or FISH analyses (Matutes et al, 1991;Mossafa et al, 1994;Rosenwald et al, 1999).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Deletions of 12p have also been found in T-PLL, using FISH and LOH methods, with a frequency of 43% (Salomon-Nguyen et al, 1998;Hetet et al, 2000). Finally, recurrent deletions or translocations of chromosome arms 6q, 13q, 17p, and monosomy 22 have occasionally been reported by standard cytogenetics or FISH analyses (Matutes et al, 1991;Mossafa et al, 1994;Rosenwald et al, 1999).…”
Section: Introductionmentioning
confidence: 93%
“…It is typically characterized by a large tumoral mass and an aggressive clinical course with a short survival (Matutes et al, 1991;Garand et al, 1998). Cytogenetic studies of T-PLL reported complex karyotypes with some recurrent chromosomal abnormalities (Brito-Babapulle et al, 1987;Matutes et al, 1991;Heinonen et al, 1994;Mossafa et al, 1994;Maljaie et al, 1998;Salomon-Nguyen et al, 1998). The Xq28 or the 14q32.1 regions are involved in translocations or inversions with the TCRA/D at 14q11.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…7,9-14 Chromosomes 14, 8, 6, 11 and X are among the most frequently involved, particularly rearrangements of bands 14q11 and 14q32, isochromosome 8q, 6q and 11q abnormalities, and t(X;14)(q28;q11). In view of the current data, rearrangements of chromosome 12p 7,10 should now be added to the list of the abnormalities associated with T-PLL. By performing FISH studies on 12p in three patients with T-PLL, rearrangements were detected including markers in two patients (A and C).…”
Section: Discussionmentioning
confidence: 99%
“…4 More recently, the question of the relationship between Sézary cell leukemia and T-PLL has been addressed. 5,6 Among the various chromosomal abnormalities described in T-PLL, rearrangements of chromosomes 14,8,6, 11 and X occurred most frequently 7 and association of several anomalies in the same patient often resulted in complex karyotypes.…”
Section: Introductionmentioning
confidence: 99%